2013
DOI: 10.1158/0008-5472.can-12-1726
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Mutation H1047R Is Associated with Response to PI3K/AKT/mTOR Signaling Pathway Inhibitors in Early-Phase Clinical Trials

Abstract: PIK3CA mutations may predict response to PI3K/AKT/mTOR inhibitors in patients with advanced cancers, but the relevance of mutation subtype has not been investigated. Patients with diverse cancers referred to the Clinical Center for Targeted Therapy were analyzed for PIK3CA and, if possible, KRAS mutations. Patients with PIK3CA mutations were treated, whenever possible, with agents targeting the PI3K/AKT/mTOR pathway. Overall, 105 (10%) of 1,012 patients tested harbored PIK3CA mutations. Sixty-six (median 3 pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
217
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 272 publications
(240 citation statements)
references
References 33 publications
12
217
4
Order By: Relevance
“…Although many early-phase trials have independently failed to identify a distinct association between clinical response and the most common alterations in the PI3K pathway (PIK3CA mutation and PTEN loss), a pooled analysis of 140 patients with various breast and gynecologic cancers treated with different PI3K/AKT/ mTOR inhibitors identified an increased rate of RECISTdefined clinical responses among patients with PIK3CA mutations (75). A follow-up study pooling 1,012 patients with diverse cancers treated with PI3K/AKT/mTOR pathway inhibitors also identified an increased rate of response among tumors with PIK3CA H1047R mutation, but not those with other PIK3CA mutations or concurrent PIK3CA and KRAS mutations (76). The findings of these association studies have sparked interest in the research community; however, additional work is required to confirm predictive biomarkers of sensitivity and resistance to each agent in large scale trials with homogenous patient populations.…”
Section: Resultsmentioning
confidence: 97%
“…Although many early-phase trials have independently failed to identify a distinct association between clinical response and the most common alterations in the PI3K pathway (PIK3CA mutation and PTEN loss), a pooled analysis of 140 patients with various breast and gynecologic cancers treated with different PI3K/AKT/ mTOR inhibitors identified an increased rate of RECISTdefined clinical responses among patients with PIK3CA mutations (75). A follow-up study pooling 1,012 patients with diverse cancers treated with PI3K/AKT/mTOR pathway inhibitors also identified an increased rate of response among tumors with PIK3CA H1047R mutation, but not those with other PIK3CA mutations or concurrent PIK3CA and KRAS mutations (76). The findings of these association studies have sparked interest in the research community; however, additional work is required to confirm predictive biomarkers of sensitivity and resistance to each agent in large scale trials with homogenous patient populations.…”
Section: Resultsmentioning
confidence: 97%
“…Analyses have shown that patients with PIK3CA mutations had a higher rate of partial responses, while coexisting PIK3CA and KRAS mutations were associated with a lack of response [55,89]. However, early evidence from the pan-PI3K inhibitor buparlisib has not shown a correlation between clinical response and PI3K/ AKT/mTOR pathway activation status [50].…”
Section: Future Clinical Perspectivesmentioning
confidence: 99%
“…Activating mutations in PIK3CA have been previously associated to responses to pathway inhibitors (38); mutations leading to activation of PIK3CB have been reported in different tumor types, but their clinical relevance remains to date unknown (31,39). Of 48 samples analyzed in this study, interestingly, five (10%) had PIK3CB aberrations, namely four patients with copy-number gains and one with an activating mutation (p.L1049R).…”
Section: Discussionmentioning
confidence: 66%